ISLAMISASI ILMU PENGETAHUAN: PRINSIP UMUM DAN RENCANA KERJA - ISMAIL RAJI' AL-FARUQI - Firda Inayah (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2020)
One of the main problems faced by Moslems today is the westernization of science. Where science is demoralized and deIslamized, so the science that should bring peace causes chaos in life. From the existing problems, this paper aims to provide a solution by presenting the concept of  Islamization of Knowledge in the view of Ismail Raji' al-Faruqi. In this study, researchers used qualitative research with descriptive methods of analysis. Based on existing research, as will be proven later, that Syed Muhammad Naquib al-Attas was the main character who inspired al-Faruqi in formulazing the idea of Islamization of Knowledge. Furthermore, as a contemporary Muslim thinker, al-Faruqi argues that the Islamization of Knowledge is a positive response to the development of modern science that tends to be secular and value-free. Interestingly, researchers found that to broaden the idea of the Islamization of Knowledge, al-Faruqi laid out the principle of tawhid as a framework of thought, methodology and way of view of Islamic life. Starting from this tauhid principle, al-Faruqi was able to formulate a work plan with five objectives and twelve steps to realize the plan. Therefore, to look at what tawhid methodology looks like as well as the framework of Islamization of Knowledge that he has formulated into an important discussion that is not biased is just passed in this study.